PENGARUH INSTITUTIONAL OWNERSHIP, PROFITABILITY DAN FAKTOR LAINNYA TERHADAP FIRM VALUE - Irfani, Dian; Sanjaya, Riki (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2024)
The aim of this research is to determine whether there is an influence of dividend policy, institutional ownership, funding policy, investment decisions, profitability, liquidity, and activity ratio as independent variables on firm value as a dependent variable in cyclical and non-cyclical consumer sector companies listed in Indonesia stock exchange. This research uses consumer cyclical and non-cyclical sector companies listed on the Indonesia Stock Exchange for the period 2020 to 2022 and uses a purposive sampling method by determining seven sample criteria to obtain a sample of 37 companies and a total of 111 data. The data analysis method used in this research is multiple linear regression. The results of this research show that the profitability and activity ratio variables have a positive effect on firm value. The liquidity variable has a negative effect on firm value. Meanwhile, the dividend policy, institutional ownership, funding policy and investment decision variables have no effect on firm value.